Incorporating a resilience lens into the social and urban transformation of informal settlements: the participatory upgrading process in villa 20, Buenos Aires (2016-2020) - Almansi, Florencia; Motta, Jorge Martín; Hardoy, Jorgelina (Cultura Económica, 2020)
Based on the experience of the socio-urban integration of Villa 20, this article suggests that upgrading processes are essentially complex and they challenge traditional public policy implementation practices. The case presented demonstrates that, when complex urban problems are addressed through citizen participation, they contribute to improve urban governance, provide comprehensive responses, and may ensure the long-term sustainability of the introduced changes. Incorporating a climate resilience lens in up grading processes of informal settlements has not been a priority in government led programs to date. However, when these processes have at their chore a deep participatory and collaborative approach they offer a window of opportunity to transform not only government practices and policies, but also influence urban designs, bring technological innovation, alternative construction practices, and adopt a more sustainable and inclusive urban development pathway.